The Effect Of The School Literacy Movement On Student's Reading Interest in SD Inpres Bulogading II Bontonompo District, Gowa Regency - Wahdaniyah, Dina; Patta, Rahmawati; Hartoto, Hartoto (Program Studi PGSD FIP UNM, 2023)
This research is an ex post facto type quantitative research which aims to determine the description of the school literacy movement, to determine the description of students' reading interest, and to determine the effect of the school literacy movement on students' reading interest at SD Inpres Bulogading II, Bontonompo District, Gowa Regency. The population in this study were all students of SD Inpres Bulogading II, Bontonompo District, Gowa Regency with a total of 129 students, and a sample size of 98 people with sampling techniques using probability sampling with simple random sampling. The data collection technique in this study used a questionnaire. Data analysis techniques with descriptive statistical analysis and inferential statistical analysis. Based on the results of descriptive statistical analysis, it was obtained that the school literacy movement had an average value of 25, and a percentage of 45% in the moderate category. Student reading interest has an average value of 26, and a percentage of 59% in the moderate category. Based on the results of inferential statistical analysis, it shows the significance of the school literacy movement on students' reading interest. It can be seen from Fhitung = 17.596 which is greater than Ftabel = 3.94 with a significant level of 5% so that Ho is rejected and Hα is accepted, it can be concluded that there is a significant influence between the school literacy movement on students' reading interest at SD Inpres Bulogading II, Bontonompo District, Kab. Gowa but has a low level of relationship degree or weak correlation because it is negative, so it has an impact where the school literacy movement does not function at school due to lack of encouragement from teachers to use existing facilities, but beyond that students actually understand the existence of the school literacy movement but students rarely or even do not utilize existing facilities at school to increase interest in reading.